A multi-proxy approach for sediment variability assessment: Application along the Colombian Caribbean coast - Nelson Rangel-Buitrago; Alex Paternina-Ramos; William J. Neal; Jesús David Pereira Ortega; Danna Lucia Anaya causado; Daniel Rincón-Martínez (Marine Geology, 2026)

From field to sky: measurement and modeling of transgenic switchgrass pollen dispersal in the atmosphere - Manu Nimmala; Hope A. Gruszewski; Regina Hanlon; Landon Bilyeu; Tyler Newton; Jessica Stockdale; Reginald J. Millwood; Charles Neal Stewart; Craig W. Powers; Shane D. Ross; Hosein Foroutan; David G. Schmale III (Environmental Monitoring and Assessment, 2026)
Accurate tracking and measurement of pollen dispersal in the atmosphere are essential for assessing cross-pollination risks, particularly in the case of genetically engineered (GE) crops. We conducted a series of unique release-recapture field studies with GE switchgrass in Oliver Springs, TN, USA. Two hundred transgenic switchgrass plants ( Panicum virgatum L. “Performer”) were planted at the center of a clear-cut field, with one block of 100 plants expressing orange fluorescent protein (OFP) under a switchgrass ubiquitin promoter (PvUBI1) and another block of 100 plants expressing OFP driven by a maize pollen-specific promoter (Zm13). Pollen was sampled from the atmosphere using fixed (ground-based) and mobile (drone-based) sampling devices at different distances from the source field, with Lagrangian stochastic dispersal simulations run for sampling periods using high-resolution wind measurements. The pollen emission rate was estimated by combining simulated and measured pollen concentrations, and strong diurnal trends were observed. Diurnal emission rate trends were positively correlated with wind speed, temperature, and vapor pressure deficit, while negatively correlated with relative humidity. In low-wind meandering conditions, incorporating changing wind direction into the dispersal modeling improved pollen emission rate estimation and model-measurement comparisons. This study assesses the effectiveness of high- and low-volume pollen samplers in relation to source strength up to 1 km from the source, enhancing understanding of pollen measurement techniques. Additionally, it is a proof-of-concept for drone-based pollen sampling and GMO pollen tracking using fluorescence measurements. Results from our experiments have significant implications for cross-pollination risk assessment, prediction, and management of airborne allergens.

Effectiveness of passive trapping and sweep netting for insect pollinator sampling in turf communities - Sara Kirby; Christine C. Fortuin; Nikolay S. Minaev; Casey J. O’Neal; David W. Held; Chih J. Wang; Gerald M. Henry; Jeffrey W. Harris; Isadora Gomes Peres de Souza; JoVonn G. Hill; James D. McCurdy (Journal of Insect Conservation, 2026)
Pollinator communities in urban and peri-urban turfgrass remain poorly characterized despite the ubiquity of lawns and growing interest in management practices that enhance floral resources within these otherwise resource-limited environments. To address this gap, we evaluated the effectiveness of active (sweep netting at multiple times of day) and passive (molasses traps and blue, white, and yellow pan traps) sampling methods for surveying insect pollinators in forb-enhanced bermudagrass plots in Mississippi and Georgia. Eight replicate plots were sampled over the course of one week at two sites, using a randomized complete block design. We identified 4,638 insect pollinator specimens representing 153 distinct taxa. Overall, sweep netting captured more individuals but tended to be biased toward larger, social taxa (e.g., Apis , Bombus ), whereas pan traps collected greater per-sample species richness and disproportionately sampled smaller, solitary taxa. Molasses traps yielded comparatively few individuals and low taxonomic diversity relative to other methods and were therefore excluded from final comparative analyses. Community composition differed significantly among sampling methods. These results demonstrate that no single method adequately captures full pollinator assemblages in forb-enhanced turfgrass systems; a complementary protocol combining sweep netting and pan trapping is recommended for comprehensive pollinator surveys in managed turf landscapes. Implications for Insect Conservation: Although conventional turfgrass monocultures generally provide limited value for insect pollinators, turfgrass-dominated landscapes are widespread in urban and peri-urban environments and therefore represent an opportunity for targeted enhancement through the incorporation of flowering forbs. However, realizing this potential requires unbiased, efficient, and reliable pollinator surveying methods that are specifically tailored to forb-enhanced turf. Here, we provide analyses that quantify the method-specific biases, temporal effects, and complementary strengths of active and passive surveying methods for monitoring pollinator abundance, richness, and community composition.

Between quiescence and crisis: Hawaiian Volcano Observatory communication and response strategies on the Island of Hawaiʻi - Katherine Mulliken; Ken Hon; David Phillips; Janet Babb; Frank Trusdell; Christina Neal; Michael Zoeller; Michael Poland; Wendy Stovall (Bulletin of Volcanology, 2026)
Over the past two centuries, eruptions of Mauna Loa volcano have damaged infrastructure and destroyed several communities on the Island of Hawaiʻi. Future eruptions will impact existing population centers and critical infrastructure, which continue to grow each year. The U.S. Geological Survey Hawaiian Volcano Observatory has developed and practiced methods to promote eruption preparedness in communities on the Island of Hawaiʻi, particularly over the past three decades during which Mauna Loa was quiescent while Kīlauea volcano erupted frequently. Here, we summarize the observatory’s efforts to increase awareness of hazards associated with Hawaiian volcanoes and describe how lessons learned during responses to past volcanic crises on Kīlauea were applied prior to and during the 2022 Mauna Loa eruption, highlighting new response communication challenges encountered during the event. Additionally, we identify potential avenues for future communication/outreach on the Island of Hawaiʻi, such as expanding efforts in communities located in high-hazard areas and striving to be more culturally and linguistically inclusive in our communication techniques.

Erratum to “Varying response of breeding waders to experimental manipulation of their habitat and predators” [J. Nat. Conserv. 72 (2023) 126353] - David J.T. Douglas; Irena Tománková; Philippa Gullett; Stephen G. Dodd; Daniel Brown; Martin Clift; Norrie Russell; Neal Warnock; Jennifer Smart; Sarah Sanders (Journal for Nature Conservation, 2026)

Toward a monocot SynBio toolkit: assessing regulatory element performance and eudicot compatibility - David B. May; Alexander C. Pfotenhauer; Bryn L. Concha; Li Li; Samantha M. Jones; Stacee A. Harbison; Lana H. Martin; Lindsey A. Clark; Alessandro Occhialini; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Insecticide application prevents honey bees from realizing benefits of native forage in an agricultural landscape - Ashley L. St. Clair; Adam G. Dolezal; Randall P. Cass; Harmen P. Hendriksma; David S. Stein; Kate E. Borchardt; Erin W. Hodgson; Matthew E. O'Neal; Amy L. Toth (Science of The Total Environment, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Water-level changes impact angler effort in a large lake: Implications for climate change - Matthew L. Maldonado; Taufique H. Mahmood; David P. Coulter; Alison A. Coulter; Steve R. Chipps; Maddy K. Siller; Michaela L. Neal; Ayon Saha; Mark A. Kaemingk (Fisheries Research, 2024)

Sensitivity of a meandering lowland river to intensive landscape management: Lateral migration rates before and after watershed-scale agricultural development - Bruce L. Rhoads; Alison M. Anders; Poushalee Banerjee; David A. Grimley; Andrew Stumpf; Neal E. Blair (Anthropocene, 2024)

Absence of Arrhythmogenicity with Biphasic Pulsed Electric Fields Delivered to Porcine Airways - Glenn R. Meininger; Robert E. Neal; David W. Hunter; William S. Krimsky (Annals of Biomedical Engineering, 2024)
Pulsed electric field (PEF) technologies treat many types of tissue. Many systems mandate synchronization to the cardiac cycle to avoid the induction of cardiac arrhythmias. Significant differences between PEF systems make the assessment of cardiac safety from one technology to another challenging. A growing body of evidence suggests that shorter duration biphasic pulses obviate the need for cardiac synchronization, even when delivered in a monopolar fashion. This study theoretically evaluates the risk profile of different PEF parameters. It then tests a monopolar, biphasic, microsecond-scale PEF technology for arrhythmogenic potential. PEF applications of increasing likelihood to induce an arrhythmia were delivered. The energy was delivered throughout the cardiac cycle, including both single and multiple packets, and then with concentrated delivery on the t-wave. There were no sustained changes to the electrocardiogram waveform or to the cardiac rhythm, despite delivering energy during the most vulnerable phase of the cardiac cycle, and delivery of multiple packets of PEF energy across the cardiac cycle. Only isolated premature-atrial contractions (PAC) were observed. This study provides evidence that certain varieties of biphasic, monopolar PEF delivery do not require synchronized energy delivery to prevent harmful arrhythmias.

Vulnerability of wells in unconfined and confined aquifers to modern contamination from flood events - Hayden Rudd; Andy Neal; David P. Genereux; Damian Shea; Elizabeth Guthrie Nichols (Science of The Total Environment, 2023)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Warming waters of the Gulf of Maine: The role of Shelf, Slope and Gulf Stream Water masses - David W. Townsend; Neal R. Pettigrew; Maura A. Thomas; Stephen Moore (Progress in Oceanography, 2023)

Fire severity effects on the herpetofaunal diversity of the Florida scrub, a biodiversity hotspot - Michelle N. Lindsay; David B. Lewis; Neal Halstead; Alison M. Gainsbury (Biodiversity and Conservation, 2023)

Comparison of Protein Particle Formation in IgG1 mAbs Formulated with PS20 Vs. PS80 When Subjected to Interfacial Dilatational Stress - Coleman Vaclaw; Kimberly Merritt; Valerie P. Griffin; Neal Whitaker; Madhushree Gokhale; David B. Volkin; Maria O. Ogunyankin; Prajnaparamita Dhar (AAPS PharmSciTech, 2023)

Varying response of breeding waders to experimental manipulation of their habitat and predators - David J.T. Douglas; Irena Tománková; Philippa Gullett; Stephen G. Dodd; Daniel Brown; Martin Clift; Norrie Russell; Neal Warnock; Jennifer Smart; Sarah Sanders (Journal for Nature Conservation, 2023)

Evaluating nutrient abatement policies for a pastorally farmed catchment-lagoon ecosystem: A New Zealand case study - Pierre C. Beukes; Marc Weeber; Mark Neal; Christophe Thiange; David F. Burger (Agriculture, Ecosystems & Environment, 2023)

Conventional loose mineral with added red clover leaf (Trifolium pratense L.) reverses vasoconstriction associated with tall fescue toxicosis in steers - Brittany E. Davis; Tracy A. Hamilton; John T. Johns; David L. Harmon; James L. Klotz; Jennifer R. Weinert-Nelson; Jack P. Goodman; John May; Huihua Ji; F. Neal Schrick; Michael D. Flythe (Animal Feed Science and Technology, 2023)

Damage assessment for the 2018 lower East Rift Zone lava flows of Kīlauea volcano, Hawaiʻi - Elinor S. Meredith; Susanna F. Jenkins; Josh L. Hayes; Natalia Irma Deligne; David Lallemant; Matthew Patrick; Christina Neal (Bulletin of Volcanology, 2022)
Cataloguing damage and its correlation with hazard intensity is one of the key components needed to robustly assess future risk and plan for mitigation as it provides important empirical data. Damage assessments following volcanic eruptions have been conducted for buildings and other structures following hazards such as tephra fall, pyroclastic density currents, and lahars. However, there are relatively limited quantitative descriptions of the damage caused by lava flows, despite the number of communities that have been devastated by lava flows in recent decades (e.g., Cumbre Vieja, La Palma, 2021; Nyiragongo, Democratic Republic of Congo, 2002 and 2021; Fogo, Cape Verde, 2014–2015). The 2018 lower East Rift Zone (LERZ) lava flows of Kīlauea volcano, Hawaiʻi, inundated 32.4 km 2 of land in the Puna District, including residential properties, infrastructure, and farmland. During and after the eruption, US Geological Survey scientists and collaborators took over 8000 aerial and ground photographs and videos of the eruption processes, deposits, and impacts. This reconnaissance created one of the largest available impact datasets documenting an effusive eruption and provided a unique opportunity to conduct a comprehensive damage assessment. Drawing on this georeferenced dataset, satellite imagery, and 2019 ground-based damage surveys, we assessed the pre-event typology and post-event condition of structures within and adjacent to the area inundated by lava flows during the 2018 LERZ eruption. We created a database of damage: each structure was assigned a newly developed damage state and data quality category value. We assessed 3165 structures within the Puna District and classified 1839 structures (58%) as destroyed, 90 structures (3%) as damaged, and 1236 (39%) as unaffected. We observed a range of damage states, affected by the structural typology and hazard characteristics. Our study reveals that structures may be damaged or destroyed beyond the lava flow margin, due to thermal effects from the lava flow, fire spread, or from exposure to a range of hazards associated with fissure eruptions, such as steam, volcanic gases, or tephra fall. This study provides a major contribution to the currently limited evidence base required to forecast future lava flow impacts and assess risk.

Amphetamine alters an EEG marker of reward processing in humans and mice - James F. Cavanagh; Sarah L. Olguin; Jo A. Talledo; Juliana E. Kotz; Benjamin Z. Roberts; John A. Nungaray; Joyce Sprock; David Gregg; Savita G. Bhakta; Gregory A. Light; Neal R. Swerdlow; Jared W. Young; et al. (Psychopharmacology, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Long-Term Changes in Terrestrial Vegetation Linked to Shifts in a Colonial Seabird Population - Matthew P. Duda; John R. Glew; Neal Michelutti; Gregory J. Robertson; William A. Montevecchi; Jennifer A. Kissinger; David C. Eickmeyer; Jules M. Blais; John P. Smol (Ecosystems, 2020)

Characterization of Concussive Events in Professional American Football Using Videogrammetry - Ann M. Bailey; Christopher P. Sherwood; James R. Funk; Jeff R. Crandall; Neal Carter; David Hessel; Stephen Beier; William Neale (Annals of Biomedical Engineering, 2020)

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Systematic review and meta-analysis of the associations between body mass index, prostate cancer, advanced prostate cancer, and prostate-specific antigen - Sean Harrison; Kate Tilling; Emma L. Turner; Richard M. Martin; Rosie Lennon; J. Athene Lane; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. L. H. Ruud Bosch; Hayley E. Jones (Cancer Causes & Control, 2020)
Purpose The relationship between body mass index (BMI) and prostate cancer remains unclear. However, there is an inverse association between BMI and prostate-specific antigen (PSA), used for prostate cancer screening. We conducted this review to estimate the associations between BMI and (1) prostate cancer, (2) advanced prostate cancer, and (3) PSA. Methods We searched PubMed and Embase for studies until 02 October 2017 and obtained individual participant data from four studies. In total, 78 studies were identified for the association between BMI and prostate cancer, 21 for BMI and advanced prostate cancer, and 35 for BMI and PSA. We performed random-effects meta-analysis of linear associations of log-PSA and prostate cancer with BMI and, to examine potential non-linearity, of associations between categories of BMI and each outcome. Results In the meta-analyses with continuous BMI, a 5 kg/m 2 increase in BMI was associated with a percentage change in PSA of − 5.88% (95% CI − 6.87 to − 4.87). Using BMI categories, compared to normal weight men the PSA levels of overweight men were 3.43% lower (95% CI − 5.57 to − 1.23), and obese men were 12.9% lower (95% CI − 15.2 to − 10.7). Prostate cancer and advanced prostate cancer analyses showed little or no evidence associations. Conclusion There is little or no evidence of an association between BMI and risk of prostate cancer or advanced prostate cancer, and strong evidence of an inverse and non-linear association between BMI and PSA. The association between BMI and prostate cancer is likely biased if missed diagnoses are not considered.

A meta‐analysis reveals temperature, dose, life stage, and taxonomy influence host susceptibility to a fungal parasite - Erin L. Sauer; Jeremy M. Cohen; Marc J. Lajeunesse; Taegan A. McMahon; David J. Civitello; Sarah A. Knutie; Karena Nguyen; Elizabeth A. Roznik; Brittany F. Sears; Scott Bessler; Bryan K. Delius; Neal Halstead; et al. (Ecology, 2020)
Complex ecological relationships, such as host–parasite interactions, are often modeled with laboratory experiments. However, some experimental laboratory conditions, such as temperature or infection dose, are regularly chosen based on convenience or convention, and it is unclear how these decisions systematically affect experimental outcomes. Here, we conducted a meta‐analysis of 58 laboratory studies that exposed amphibians to the pathogenic fungus Batrachochytrium dendrobatidis (Bd) to understand better how laboratory temperature, host life stage, infection dose, and host species affect host mortality. We found that host mortality was driven by thermal mismatches: hosts native to cooler environments experienced greater Bd‐induced mortality at relatively warm experimental temperatures and vice versa. We also found that Bd dose positively predicted Bd‐induced host mortality and that the superfamilies Bufonoidea and Hyloidea were especially susceptible to Bd. Finally, the effect of Bd on host mortality varied across host life stages, with larval amphibians experiencing lower risk of Bd‐induced mortality than adults or metamorphs. Metamorphs were especially susceptible and experienced mortality when inoculated with much smaller Bd doses than the average dose used by researchers. Our results suggest that when designing experiments on species interactions, researchers should carefully consider the experimental temperature, inoculum dose, and life stage, and taxonomy of the host species.

Corticomotor function is associated with quadriceps rate of torque development in individuals with ACL surgery - Sarah A. Scheurer; David A. Sherman; Neal R. Glaviano; Christopher D. Ingersoll; Grant E. Norte (Experimental Brain Research, 2020)

A global review and meta-analysis of applications of the freshwater Fish Invasiveness Screening Kit - Lorenzo Vilizzi; Gordon H. Copp; Boris Adamovich; David Almeida; Joleen Chan; Phil I. Davison; Samuel Dembski; F. Güler Ekmekçi; Árpád Ferincz; Sandra C. Forneck; Jeffrey E. Hill; Jeong-Eun Kim; et al. (Reviews in Fish Biology and Fisheries, 2019)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Impacts of thermal mismatches on chytrid fungus Batrachochytrium dendrobatidis prevalence are moderated by life stage, body size, elevation and latitude - Jeremy M. Cohen; Taegan A. McMahon; Chloe Ramsay; Elizabeth A. Roznik; Erin L. Sauer; Scott Bessler; David J. Civitello; Bryan K. Delius; Neal Halstead; Sarah A. Knutie; Karena H. Nguyen; Nicole Ortega; et al. (Ecology Letters, 2019)
Global climate change is increasing the frequency of unpredictable weather conditions; however, it remains unclear how species‐level and geographic factors, including body size and latitude, moderate impacts of unusually warm or cool temperatures on disease. Because larger and lower‐latitude hosts generally have slower acclimation times than smaller and higher‐latitude hosts, we hypothesised that their disease susceptibility increases under ‘thermal mismatches’ or differences between baseline climate and the temperature during surveying for disease. Here, we examined how thermal mismatches interact with body size, life stage, habitat, latitude, elevation, phylogeny and International Union for Conservation of Nature (IUCN) conservation status to predict infection prevalence of the chytrid fungus Batrachochytrium dendrobatidis ( Bd ) in a global analysis of 32 291 amphibian hosts. As hypothesised, we found that the susceptibility of larger hosts and hosts from lower latitudes to Bd was influenced by thermal mismatches. Furthermore, hosts of conservation concern were more susceptible than others following thermal mismatches, suggesting that thermal mismatches might have contributed to recent amphibian declines.

Spatiotemporal remote sensing of ecosystem change and causation across Alaska - Neal J. Pastick; M. Torre Jorgenson; Scott J. Goetz; Benjamin M. Jones; Bruce K. Wylie; Burke J. Minsley; Hélène Genet; Joseph F. Knight; David K. Swanson; Janet C. Jorgenson (Global Change Biology, 2019)
Contemporary climate change in Alaska has resulted in amplified rates of press and pulse disturbances that drive ecosystem change with significant consequences for socio‐environmental systems. Despite the vulnerability of Arctic and boreal landscapes to change, little has been done to characterize landscape change and associated drivers across northern high‐latitude ecosystems. Here we characterize the historical sensitivity of Alaska's ecosystems to environmental change and anthropogenic disturbances using expert knowledge, remote sensing data, and spatiotemporal analyses and modeling. Time‐series analysis of moderate—and high‐resolution imagery was used to characterize land‐ and water‐surface dynamics across Alaska. Some 430,000 interpretations of ecological and geomorphological change were made using historical air photos and satellite imagery, and corroborate land‐surface greening, browning, and wetness/moisture trend parameters derived from peak‐growing season Landsat imagery acquired from 1984 to 2015. The time series of change metrics, together with climatic data and maps of landscape characteristics, were incorporated into a modeling framework for mapping and understanding of drivers of change throughout Alaska. According to our analysis, approximately 13% (~174,000 ± 8700 km 2 ) of Alaska has experienced directional change in the last 32 years (±95% confidence intervals). At the ecoregions level, substantial increases in remotely sensed vegetation productivity were most pronounced in western and northern foothills of Alaska, which is explained by vegetation growth associated with increasing air temperatures. Significant browning trends were largely the result of recent wildfires in interior Alaska, but browning trends are also driven by increases in evaporative demand and surface‐water gains that have predominately occurred over warming permafrost landscapes. Increased rates of photosynthetic activity are associated with stabilization and recovery processes following wildfire, timber harvesting, insect damage, thermokarst, glacial retreat, and lake infilling and drainage events. Our results fill a critical gap in the understanding of historical and potential future trajectories of change in northern high‐latitude regions.

Developing new age-specific prostate-specific antigen thresholds for testing for prostate cancer - Rebecca Gilbert; Kate Tilling; Richard M. Martin; J. Athene Lane; Michael Davis; Freddie C. Hamdy; David E. Neal; Jenny L. Donovan; Chris Metcalfe (Cancer Causes & Control, 2018)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Shifting paradigms in restoration of the world's coral reefs - Madeleine J. H. van Oppen; Ruth D. Gates; Linda L. Blackall; Neal Cantin; Leela J. Chakravarti; Wing Y. Chan; Craig Cormick; Angela Crean; Katarina Damjanovic; Hannah Epstein; Peter L. Harrison; Thomas A. Jones; et al. (Global Change Biology, 2017)
Many ecosystems around the world are rapidly deteriorating due to both local and global pressures, and perhaps none so precipitously as coral reefs. Management of coral reefs through maintenance (e.g., marine‐protected areas, catchment management to improve water quality), restoration, as well as global and national governmental agreements to reduce greenhouse gas emissions (e.g., the 2015 Paris Agreement) is critical for the persistence of coral reefs. Despite these initiatives, the health and abundance of corals reefs are rapidly declining and other solutions will soon be required. We have recently discussed options for using assisted evolution (i.e., selective breeding, assisted gene flow, conditioning or epigenetic programming, and the manipulation of the coral microbiome) as a means to enhance environmental stress tolerance of corals and the success of coral reef restoration efforts. The 2014–2016 global coral bleaching event has sharpened the focus on such interventionist approaches. We highlight the necessity for consideration of alternative (e.g., hybrid) ecosystem states, discuss traits of resilient corals and coral reef ecosystems, and propose a decision tree for incorporating assisted evolution into restoration initiatives to enhance climate resilience of coral reefs.

Post-diagnosis serum insulin-like growth factors in relation to dietary and lifestyle changes in the Prostate testing for cancer and Treatment (ProtecT) trial - Vanessa Er; Kalina Biernacka; Andrew J. Simpkin; Richard M. Martin; Mona Jeffreys; Pauline Emmett; Rebecca Gilbert; Kerry N. L. Avery; Eleanor Walsh; Michael Davis; Jenny L. Donovan; David E. Neal; et al. (Cancer Causes & Control, 2017)
Purpose The insulin-like growth factor (IGF) system is modifiable by diet and lifestyle, and has been linked to prostate cancer development and progression. Methods We conducted a prospective cohort study of 621 men diagnosed with localized prostate cancer to investigate the associations of dietary and lifestyle changes with post-diagnosis circulating levels of IGF-I and IGFBP-3. We used analysis of covariance to estimate the associations, controlling for baseline IGF-I or IGFBP-3, respectively. Results Mean IGF-I levels were 6.5% (95% CI −12.8, −0.3%, p = 0.04) lower in men who decreased their protein intake after diagnosis compared to men who did not change. Men who changed their fruit and vegetable intake had lower IGF-I levels compared to non-changers [Decreased intake: −10.1%, 95% CI −18.4, −1.8%, p = 0.02; Increased intake: −12.0%, 95% CI −18.4, −1.8%, p = 0.002]. IGFBP-3 was 14.6% (95% CI −24.5, −4.8%, p = 0.004) lower in men who achieved a healthy body mass index after diagnosis. Men who became inactive had 9.5% higher average IGF-I levels (95% CI 0.1, 18.9%, p = 0.05). Conclusions Decreased protein intake and body mass index, and increased physical activity and fruit and vegetable intake, following a prostate cancer diagnosis were associated with reduced post-diagnosis serum IGF-I and IGFBP-3. Counterintuitively, reduced fruit and vegetable intake was also associated with reduced IGF-I, but with weak statistical support, possibly implicating chance. If confirmed in other studies, our findings may inform potential lifestyle interventions in prostate cancer. ProtecT was registered at International Standard Randomised Controlled Trial Registry, http://isrctn.org as ISRCTN20141297.

Investigating the prostate specific antigen, body mass index and age relationship: is an age–BMI-adjusted PSA model clinically useful? - Sean Harrison; Kate Tilling; Emma L. Turner; J. Athene Lane; Andrew Simpkin; Michael Davis; Jenny Donovan; Freddie C. Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2016)

A class of non-linear exposure-response models suitable for health impact assessment applicable to large cohort studies of ambient air pollution - Masoud M. Nasari; Mieczysław Szyszkowicz; Hong Chen; Daniel Crouse; Michelle C. Turner; Michael Jerrett; C. Arden Pope; Bryan Hubbell; Neal Fann; Aaron Cohen; Susan M. Gapstur; W. Ryan Diver; et al. (Air Quality, Atmosphere & Health, 2016)

A randomized, placebo-controlled pilot trial of the delta opioid receptor agonist AZD2327 in anxious depression - Erica M. Richards; Daniel C. Mathews; David A. Luckenbaugh; Dawn F. Ionescu; Rodrigo Machado-Vieira; Mark J. Niciu; Wallace C. Duncan; Neal M. Nolan; Jose A. Franco-Chaves; Thomas Hudzik; Carla Maciag; Shuang Li; et al. (Psychopharmacology, 2016)

Mineral nutrition and specific leaf area of plants under contrasting long-term fire frequencies: a case study in a mesic savanna in Australia - Marcelo Claro de Souza; Davi Rodrigo Rossatto; Garry David Cook; Ryosuke Fujinuma; Neal William Menzies; Leonor Patricia Cerdeira Morellato; Gustavo Habermann (Trees, 2016)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Reply to Discussion: The timing of gold mineralization across the eastern Yilgarn Craton using U–Pb geochronology of hydrothermal phosphate minerals - Noreen M. Vielreicher; David I. Groves; Neal J. McNaughton (Mineralium Deposita, 2015)

Methods and measurement variance for field estimations of coral colony planar area using underwater photographs and semi-automated image segmentation - Benjamin P. Neal; Tsung-Han Lin; Rivah N. Winter; Tali Treibitz; Oscar Beijbom; David Kriegman; David I. Kline; B. Greg Mitchell (Environmental Monitoring and Assessment, 2015)

The timing of gold mineralization across the eastern Yilgarn craton using U–Pb geochronology of hydrothermal phosphate minerals - Noreen Vielreicher; David Groves; Neal McNaughton; Ian Fletcher (Mineralium Deposita, 2015)

Associations of vitamin D pathway genes with circulating 25-hydroxyvitamin-D, 1,25-dihydroxyvitamin-D, and prostate cancer: a nested case–control study - Rebecca Gilbert; Carolina Bonilla; Chris Metcalfe; Sarah Lewis; David M. Evans; William D. Fraser; John P. Kemp; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. Athene Lane; George Davey Smith; et al. (Cancer Causes & Control, 2015)

Stable H–C–O isotope and trace element geochemistry of the Cummins Range Carbonatite Complex, Kimberley region, Western Australia: implications for hydrothermal REE mineralization, carbonatite evolution and mantle source regions - Peter J. Downes; Attila Demény; György Czuppon; A. Lynton Jaques; Michael Verrall; Marcus Sweetapple; David Adams; Neal J. McNaughton; Lalchand G. Gwalani; Brendan J. Griffin (Mineralium Deposita, 2014)

Biologic Comparison of Inhaled Insulin Formulations: ExuberaTM and Novel Spray-Dried Engineered Particles of Dextran-10 - Philip J. Kuehl; Alan Cherrington; Dan E. Dobry; Dale Edgerton; Dwayne T. Friesen; Charles Hobbs; Chet L. Leach; Brice Murri; Doss Neal; David K. Lyon; David T. Vodak; Matthew D. Reed (AAPS PharmSciTech, 2014)

Men with prostate cancer make positive dietary changes following diagnosis and treatment - Kerry N. L. Avery; Jenny L. Donovan; Rebecca Gilbert; Michael Davis; Pauline Emmett; Liz Down; Steven Oliver; David E. Neal; Freddie C. Hamdy; J. Athene Lane (Cancer Causes & Control, 2013)

The public health context for PM2.5 and ozone air quality trends - Neal Fann; David Risley (Air Quality, Atmosphere & Health, 2013)

Associations of adiponectin and leptin with stage and grade of PSA-detected prostate cancer: the ProtecT study - Anya Burton; Richard M. Martin; Jeff Holly; J. Athene Lane; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; Kate Tilling (Cancer Causes & Control, 2013)

Insulin-like growth factors (IGFs) and IGF-binding proteins in active monitoring of localized prostate cancer: a population-based observational study - Mari-Anne Rowlands; Kate Tilling; Jeff M. P. Holly; Chris Metcalfe; David Gunnell; Athene Lane; Michael Davis; Jenny Donovan; Freddie Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2013)

Associations of circulating retinol, vitamin E, and 1,25-dihydroxyvitamin D with prostate cancer diagnosis, stage, and grade - Rebecca Gilbert; Chris Metcalfe; William D. Fraser; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Richard M. Martin (Cancer Causes & Control, 2012)

A cross-sectional analysis of the association between diet and insulin-like growth factor (IGF)-I, IGF-II, IGF-binding protein (IGFBP)-2, and IGFBP-3 in men in the United Kingdom - Nicholas J. Young; Chris Metcalfe; David Gunnell; Mari-Anne Rowlands; J. Athene Lane; Rebecca Gilbert; Kerry N. L. Avery; Michael Davis; David E. Neal; Freddie C. Hamdy; Jenny Donovan; Richard M. Martin; et al. (Cancer Causes & Control, 2012)

Climate change projections and stratosphere–troposphere interaction - Adam A. Scaife; Thomas Spangehl; David R. Fereday; Ulrich Cubasch; Ulrike Langematz; Hideharu Akiyoshi; Slimane Bekki; Peter Braesicke; Neal Butchart; Martyn P. Chipperfield; Andrew Gettelman; Steven C. Hardiman; et al. (Climate Dynamics, 2012)

Predictors of 25-hydroxyvitamin D and its association with risk factors for prostate cancer: evidence from the Prostate testing for cancer and Treatment study - Rebecca Gilbert; Richard M. Martin; William D. Fraser; Sarah Lewis; Jenny Donovan; Freddie Hamdy; David E. Neal; J. Athene Lane; Chris Metcalfe (Cancer Causes & Control, 2012)

Serum insulin-like growth factors and mortality in localised and advanced clinically detected prostate cancer - Mari-Anne Rowlands; Jeff M. P. Holly; Freddie Hamdy; Joshua Phillips; Louise Goodwin; Gemma Marsden; David Gunnell; Jenny Donovan; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2012)

Archaean gold mineralization synchronous with late cratonization of the Western Dharwar Craton, India: 2.52 Ga U–Pb ages of hydrothermal monazite and xenotime in gold deposits - D. Srinivasa Sarma; Ian R. Fletcher; Birger Rasmussen; Neal J. McNaughton; M. Ram Mohan; David I. Groves (Mineralium Deposita, 2011)

The relation between adiposity throughout the life course and variation in IGFs and IGFBPs: evidence from the ProtecT (Prostate testing for cancer and Treatment) study - Mari-Anne Rowlands; Jeff M. P. Holly; David Gunnell; Rebecca Gilbert; Jenny Donovan; J. Athene Lane; Gemma Marsden; Simon M. Collin; Freddie Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2010)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

Age-dependent cognitive impairment in a Drosophila Fragile X model and its pharmacological rescue - Catherine H. Choi; Sean M. J. McBride; Brian P. Schoenfeld; David A. Liebelt; David Ferreiro; Neal J. Ferrick; Paul Hinchey; Maria Kollaros; Rebecca L. Rudominer; Allison M. Terlizzi; Eric Koenigsberg; Yan Wang; et al. (Biogerontology, 2010)

Neural basis for a heritable phenotype: differences in the effects of apomorphine on startle gating and ventral pallidal GABA efflux in male Sprague–Dawley and Long–Evans rats - Ying Qu; Richard L. Saint Marie; Michelle R. Breier; David Ko; David Stouffer; Loren H. Parsons; Neal R. Swerdlow (Psychopharmacology, 2009)

Rapid Assessment of Lignin Content and Structure in Switchgrass (Panicum virgatum L.) Grown Under Different Environmental Conditions - David G. J. Mann; Nicole Labbé; Robert W. Sykes; Kristen Gracom; Lindsey Kline; Isabella M. Swamidoss; Jason N. Burris; Mark Davis; C. Neal Stewart (BioEnergy Research, 2009)

An Improved Tissue Culture System for Embryogenic Callus Production and Plant Regeneration in Switchgrass (Panicum virgatum L.) - Jason N. Burris; David G. J. Mann; Blake L. Joyce; C. Neal Stewart (BioEnergy Research, 2009)

Distribution of nitrogen-15 tracers applied to the canopy of a mature spruce-hemlock stand, Howland, Maine, USA - David Bryan Dail; David Y. Hollinger; Eric A. Davidson; Ivan Fernandez; Herman C. Sievering; Neal A. Scott; Elizabeth Gaige (Oecologia, 2009)

Effect of PCR amplicon size on assessments of clone library microbial diversity and community structure - Julie A. Huber; Hilary G. Morrison; Susan M. Huse; Phillip R. Neal; Mitchell L. Sogin; David B. Mark Welch (Environmental Microbiology, 2009)
Summary PCR‐based surveys of microbial communities commonly use regions of the small‐subunit ribosomal RNA (SSU rRNA) gene to determine taxonomic membership and estimate total diversity. Here we show that the length of the target amplicon has a significant effect on assessments of microbial richness and community membership. Using operational taxonomic unit (OTU)‐ and taxonomy‐based tools, we compared the V6 hypervariable region of the bacterial SSU rRNA gene of three amplicon libraries of c. 100, 400 and 1000 base pairs (bp) from each of two hydrothermal vent fluid samples. We found that the smallest amplicon libraries contained more unique sequences, higher diversity estimates and a different community structure than the other two libraries from each sample. We hypothesize that a combination of polymerase dissociation, cloning bias and mispriming due to secondary structure accounts for the differences. While this relationship is not linear, it is clear that the smallest amplicon libraries contained more different types of sequences, and accordingly, more diverse members of the community. Because divergent and lower abundant taxa can be more readily detected with smaller amplicons, they may provide better assessments of total community diversity and taxonomic membership than longer amplicons in molecular studies of microbial communities.

Sonic hedgehog mutations identified in holoprosencephaly patients can act in a dominant negative manner - Samer Singh; Robert Tokhunts; Valerie Baubet; John A. Goetz; Zhen Jane Huang; Neal S. Schilling; Kendall E. Black; Todd A. MacKenzie; Nadia Dahmane; David J. Robbins (Human Genetics, 2009)

Differential expression of genes in soybean in response to the causal agent of Asian soybean rust (Phakopsora pachyrhizi Sydow) is soybean growth stage-specific - Dilip R. Panthee; James J. Marois; David L. Wright; Dario Narváez; Joshua S. Yuan; C. Neal Stewart (Theoretical and Applied Genetics, 2009)

Mitigating Climate Change with Managed Forests: Balancing Expectations, Opportunity, and Risk - David G. Ray; Robert S. Seymour; Neal A. Scott; William S. Keeton (Journal of Forestry, 2009)

Realistic expectations of prepulse inhibition in translational models for schizophrenia research - Neal R. Swerdlow; Martin Weber; Ying Qu; Gregory A. Light; David L. Braff (Psychopharmacology, 2008)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Uraniferous diagenetic xenotime in northern Australia and its relationship to unconformity-associated uranium mineralisation - Daniela A. Vallini; David I. Groves; Neal J. McNaughton; Ian R. Fletcher (Mineralium Deposita, 2007)

Laser-Induced Fluorescence Imaging and Spectroscopy of GFP Transgenic Plants - C. Neal Stewart; Reginald J. Millwood; Matthew D. Halfhill; Mentewab Ayalew; Vinitha Cardoza; Mitra Kooshki; Gene A. Capelle; Kevin R. Kyle; David Piaseki; Gregory McCrum; John Di Benedetto (Journal of Fluorescence, 2005)

A comprehensive SNP-based genetic analysis of inbred mouse strains - Shirley Tsang; Zhonghe Sun; Brian Luke; Claudia Stewart; Nicole Lum; Melissa Gregory; Xiaolin Wu; Marianne Subleski; Nancy A. Jenkins; Neal G. Copeland; David J. Munroe (Mammalian Genome, 2005)

Changes in Carbon Storage and Net Carbon Exchange One Year After an Initial Shelterwood Harvest at Howland Forest, ME - Neal A. Scott; Charles A. Rodrigues; Holly Hughes; John T. Lee; Eric A. Davidson; D. Bryan Dail; Phil Malerba; David Y. Hollinger (Environmental Management, 2004)

Geological and SHRIMP II U-Pb constraints on the age and origin of the Breves Cu-Au-(W-Bi-Sn) deposit, Carajs, Brazil - Ian R. Fletcher; Bernardino Ribeiro Figueiredo; Jssica Beatriz Carvalho; Jos Luzimar Rego; Alfredo Rossetto Nunes; Fernando Henrique Bucco Tallarico; Neal Jesse McNaughton; David Ian Groves (Mineralium Deposita, 2004)

Age constraints on Tarkwaian palaeoplacer and lode-gold formation in the Tarkwa-Damang district, SW Ghana - Jon-Philippe Pigois; David I. Groves; Ian R. Fletcher; Neal J. McNaughton; Lawrence W. Snee (Mineralium Deposita, 2003)

Reply to the discussion on "Gold deposits of the Tapajós and Alta Floresta domains, Tapajós–Parima orogenic belt, Amazon Craton, Brazil" (Mineralium Deposita 36:278–299, 2001) by Dreher AM, Mach SRF, Martini SL - João Santos; David Groves; Léo Hartmann; Márcia Moura; Neal McNaughton (Mineralium Deposita, 2002)

Effects of aerobic fitness training on human cortical function - Arthur F. Kramer; Stanley Colcombe; Kirk Erickson; Artem Belopolsky; Edward McAuley; Neal J. Cohen; Andrew Webb; Gerald J. Jerome; David X. Marquez; Tracey M. Wszalek (Journal of Molecular Neuroscience, 2002)

Physical and chemical limnology of 34 ultra-oligotrophic lakes and ponds near Wynniatt Bay, Victoria Island, Arctic Canada - Neal Michelutti; Marianne S.V. Douglas; David R.S. Lean; John P. Smol (Hydrobiologia, 2002)

Pharmacological studies of prepulse inhibition models of sensorimotor gating deficits in schizophrenia: a decade in review - Mark A. Geyer; Kirsten Krebs-Thomson; David L. Braff; Neal R. Swerdlow (Psychopharmacology, 2001)

Human studies of prepulse inhibition of startle: normal subjects, patient groups, and pharmacological studies - David L. Braff; Mark A. Geyer; Neal R. Swerdlow (Psychopharmacology, 2001)

Gold deposits of the Tapajós and Alta Floresta Domains, Tapajós–Parima orogenic belt, Amazon Craton, Brazil - João Orestes Schneider Santos; David Ian Groves; Léo Afraneo Hartmann; Márcia Abrahão Moura; Neal Jesse McNaughton (Mineralium Deposita, 2001)

SUPPRESSION OF ANTIGEN-SPECIFIC LYMPHOCYTE ACTIVATION IN MODELED MICROGRAVITY - DAVID COOPER; MICHAEL W. PRIDE; ERIC L. BROWN; DIANA RISIN; NEAL R. PELLIS (In Vitro Cellular & Developmental Biology - Animal, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Changes in gravity inhibit lymphocyte locomotion through type I collagen - Neal R. Pellis; Thomas J. Goodwin; Diana Risin; Bradley W. McIntyre; Roland P. Pizzini; David Cooper; Tacey L. Baker; Glenn F. Spaulding (In Vitro Cellular & Developmental Biology - Animal, 1997)

A precision measure of anatomic dead space: Theory - Neal B. Kindig; David R. Hazlett (Annals of Biomedical Engineering, 1978)